Enhanced Light Emission Performance of Mixed Cation Perovskite Films—The Effect of Solution Stoichiometry on Crystallization. Issue 21 (20th August 2021) - Liu, Fangzhou; Qin, Xinshun; Han, Bing; Chan, Christopher C. S.; Ma, Chao; Leung, Tik Lun; Chen, Wei; He, Yanling; Lončarić, Ivor; Grisanti, Luca; Ovčar, Juraj; Skoko, Željko; et al.
Abstract: The performance of quasi‐2D perovskite light emitting diodes (LEDs) with mixed small cations, cesium and formamidinium (FA), is significantly affected by their ratio. The best devices obtained for Cs:FA ratio of 1:1 exhibit a maximum external quantum efficiency (EQE) of 12.1%, maximum luminance of 15 070 cd m −2 and maximum current efficiency of 46.1 cd A −1, which is significantly higher (about 3 times) compared to devices with FA only (maximum EQE of 4.1%, maximum luminance of 4521 cd m −2 ) and Cs‐only (maximum EQE of 4.0%, maximum luminance of 4886 cd m −2 ). The photoluminescence quantum yield of the Cs:FA 1:1 sample is similarly enhanced, 21.3% compared 5.4% and 6%, for FA‐only and Cs‐only samples, respectively. It can be observed that the Cs:FA ratio significantly affects the crystallization of the perovskite, with the optimal 1:1 ratio resulting in the formation of tetragonal Cs0.5 FA0.5 PbBr3 phase (different from cubic FAPbBr3 and orthorhombic CsPbBr3 ) with pronounced preferential orientation as well as a significant reduction in the trap density, which leads to a substantial improvement in the light‐emitting performance. Abstract : Mixing of small cations, cesium and formamidinium (FA), alters the crystallization of hexylammonium‐based quasi‐2D perovskite films, resulting in significant improvement in the light‐emitting performance, with maximum external quantum efficiency (12.1%) and maximum luminance (15070 cd m −2 ) about three times higher compared to single cation devices.